English culture and the decline of the industrial spirit, 1850-1980 - Wiener, Martin J. (Cambridge University Press, 2004)
England was the world's first great industrial nation. Yet the English have never been comfortable with industrialism. Drawing upon a wide array of sources, Martin Wiener explores the English ambivalence to modern industrial society. His work reveals a pervasive middle- and upper-class frame of mind hostile to industrialism and economic growth. From the middle of the nineteenth century to the present, this frame of mind shaped a broad spectrum of cultural expression, including literature, journalism, and architecture, as well as social, historical, and economic thought. In this edition, Wiener reflects on the original debate surrounding the work and examines the historiography of the last few decades. Written in a graceful and accessible style, with reference to a broad range of people and ideas, this book will be of interest to all readers who wish to understand the development - and predicament - of modern England